Central nervous system blast crisis of chronic myeloid leukaemia misdiagnosed as tubercular meningitis. (12th June 2018) - Kumawat, Banshi Lal; Sharma, Chandra Mohan; Saini, Pankaj Kumar; Garg, Ankur
Abstract : Chronic Myeloid Leukaemia (CML) presenting with isolated Central Nervous System (CNS) blast crisis is an uncommon entity. A 22-year-old man, diagnosed with chronic phase CML in 2011 and was in haematological and cytogenetic remission until July 2016, had acute onset headache and vomiting with meningeal signs and was admitted elsewhere, investigated by brain imaging and cerebrospinal fluid (CSF) analysis and suspected to have tubercular meningitis, for which steroids and antitubercular medications were started. The patient's sensorium further deteriorated, and Ventriculoperitoneal shunt surgery was done for hydrocephalus by a neurosurgeon. After 2 months of the illness, he was admitted to our hospital with a persistent headache, vomiting and altered sensorium. CSF for cytospin confirmed myeloid blasts. He was still in haematological remission. So, a diagnosis of isolated CNS blast crisis was made. The patient was started on triple intrathecal chemotherapy and cranial radiotherapy. He had improvement with treatment and is still in remission.